Characterization and function of a cathepsin B in red crayfish (Procambarus clarkii) following lipopolysaccharide challenge. (September 2016) - Dai, Li-Shang; Sun, Yu; Sun, Yu-Xuan; Zhu, Bao-Jian; Liu, Chao-Liang
Abstract: Cathepsin B is a lysosomal cysteine protease of the papain-like enzyme family with multiple biological functions. In the present study, a cathepsin B gene (named PcCTSB ) was cloned and characterized from the red crayfish, Procambarus clarkii . The cDNA fragments of PcCTSB was 990 bp in length. It encoded a putative protein of 329 amino acid residues with predicted molecular weight of 36.4 kDa and isoelectric point of 7.020. Sequence alignment revealed that PcCTSB protein is 53.6%–80.4% identical with those from other 10 species. The predicted tertiary structure of PcCTSB protein was highly similar to that of animals. The results of the phylogenetic analysis indicated that the PcCTSB protein could be clustered with the Eriocheir sinensis cathepsin B protein. The recombinant protein of PcCTSB was expressed successfully in Escherichia coli cells. The mRNA expressions of PcCTSB were detected in all tested tissues, particularly high in the hepatopancreas. After lipopolysaccharide (LPS) challenge, the expression levels of PcCTSB were up-regulated significantly at different time points compared with control. Our results suggested that the PcCTSB might play an important role in defending against the pathogenes infection. Highlights: A cathepsin B from Procambarus clarkii ( PcCTSB ) was identified and characterized. The expression profiles of PcCTSB in various tissues were investigated. The transcripts of PcCTSB were performed in response to LPS challenge.